Quality of Life in Mothers of Children with Cerebral Palsy - Alma Glinac; Lejla Matović; Azra Delalić; Lejla Mešalić (Acta Clinica Croatica, 2017)
The aim of the study was to investigate whether there is difference in the quality of life between mothers of children with cerebral palsy and mothers of healthy children, as well as whether the quality of life in mothers of children with cerebral palsy depends on their level of education, child’s mobility and child’s functional status. A total of 141 mothers participated in the research. Mothers were divided into two groups, 71 mothers of children with cerebral palsy and 70 mothers of healthy children from the Tuzla Canton (Bosnia and Herzegovina). A multidimensional questionnaire PedsQL™ 2.0 Family Impact Mode was used for assessment of the impact of pediatric chronic health condition on the mothers’ functioning. Th e level of functional disability of the child was measured by the Gross Motor Function Classification System (GMFCS levels I-V) scale. Mothers of children with cerebral palsy had poorer quality of life than mothers of healthy children in all investigated domains. In relation to mobility of the child, the quality of life was worse in mothers whose children did not move in the area of social functioning in comparison to mothers whose children had the ability to move independently. A statistically significant negative correlation existed between functional status of a child measured with GMFCS and social functioning of mothers, mothers’ daily activities, parental functioning, family functioning, and overall quality of life of mothers.